1976
DOI: 10.1128/aac.10.4.768
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Gentamicin, Tobramycin, Sisomicin, and Netilmicin

Abstract: The antimicrobial activity of gentamicin, tobramycin, sisomicin, and netilmicin (Sch 20569) was compared against 150 strains of organisms. Netilmicin was shown to be the least effective against Pseudomonas strains but to have slightly better activity against Staphylococcus aureus and Escherichia coli than the other agents. The effect of calcium and magnesium in enhancing the differences in activity of these aminoglycosides against Pseudomonas strains was also demonstrated.This study was carried out to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…20569), an ethyl deriva tive of sisomicin, was reported to be effec tive in vitro against aerobic gram-negative bacilli [1][2][3][4][5][6][7][8][9][10][11][12], It has been suggested that it may be less oto-and nephrotoxic than gen tamicin [6,7]. In clinical trials, this anti biotic was found to attain higher serum lev els than gentamicin [6,7], It is controversial if netilmicin is any more effective than gen tamicin against Pseudomonas aeruginosa and other gentamicin-resistant gram-nega tive bacilli [3,5,12].…”
Section: Introductionmentioning
confidence: 99%
“…20569), an ethyl deriva tive of sisomicin, was reported to be effec tive in vitro against aerobic gram-negative bacilli [1][2][3][4][5][6][7][8][9][10][11][12], It has been suggested that it may be less oto-and nephrotoxic than gen tamicin [6,7]. In clinical trials, this anti biotic was found to attain higher serum lev els than gentamicin [6,7], It is controversial if netilmicin is any more effective than gen tamicin against Pseudomonas aeruginosa and other gentamicin-resistant gram-nega tive bacilli [3,5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Netilmicin has been reported to have considerable activity against gram-negative clinical isolates (2,3,5,6,(8)(9)(10) and to be effective against some gentamicin-resistant strains (3,(7)(8)(9). This in vitro study evaluates the correlation between netilmicin agar dilution minimal inhibitory concentrations (MICs) and disk diffusion zone diameters.…”
mentioning
confidence: 99%